Essential business mathematics : theory of interest - business calculus - Nocon, Rizaldi C. (Quezon City, Philippines : C & E Publishing Inc., 2013)
This book discusses the mathematical concepts needed to allow the student to work with certain business applications.
CHAPTER 1. Types of interest -- 2. Annuity -- 3. Lines and quadratic curves -- 4. Applications of lines and quadratic curves -- 5. Limit of a function -- 6. Differential calculus -- 7. Application of derivatives -- 8. Integral calculus -- Appendices.
Includes bibliographical references.
Keywords: BUSINESS MATHEMATICS